Spatial and temporal characterization of epiphytic microbial communities associated with Eurasian watermilfoil: a highly invasive macrophyte in North America. Issue 12 (3rd September 2018) - Mathai, Prince P; Dunn, Hannah M; Magnone, Paolo; Brown, Clairessa M; Chun, Chan Lan; Sadowsky, Michael J
ABSTRACT: Bacterial communities that inhabit the surface of aquatic plants are thought to play a critical role in relation to host fitness and function. However, little is known about their structure and dynamics in comparison with those of bacterioplankton. In this study, we performed a comprehensive spatial and temporal characterization of epibacterial communities associated with Eurasian watermilfoil (EWM; Myriophyllum spicatum ), an invasive macrophyte, which has established itself in thousands of lakes across North America. EWM samples were collected from 10 lakes in Minnesota, once a month, for six consecutive months, along with surrounding water and sediment. High-throughput DNA sequencing analyses, performed on all samples (n = 522) using the Illumina platform, indicated that EWM-associated epibacterial communities were distinct from those found in water and sediment. EWM-specific microbiota was comprised of operational taxonomic units classified to the families Rhodobacteraceae, Comamonadaceae, Cyanobacteria Subsection I Family I, Aeromonadaceae, Planctomycetaceae, Sphingomonadaceae and Verrucomicrobiaceae . In addition, several identified taxa were overrepresented in EWM samples when compared to water and sediment. Amongst all the environmental factors examined, water temperature had the greatest influence on epibacterial community structure. Our findings suggest that EWM harbor specific, but temporally adapted, epibacterial communities that are potentially involved in host–microbe interactions. Abstract : Amplicon-based DNA sequencing revealed that bacterial communities associated with Eurasian watermilfoil are distinct from those in water and sediment, but temporally adapted.